P002 Exclusive Enteral Nutrition, the gut microbiome and corticosteroid response in patients with acute severe colitis. (30th January 2023) - Bajaj, A; Markandey, M; Vuyyuru, S; Mohta, S; Singh, M; Verma, M; Kumar, S; Kante, B; Kumar, P; Makharia, G; Kedia, S; Travis, S; et al.
Abstract: Background: Supplementation with exclusive enteral nutrition (EEN) in addition to standard of care with intravenous corticosteroids (SOC) augments the steroid response in patients with acute severe ulcerative colitis (ASUC). EEN is known to alter gut microbial composition. The present study identifies changes in gut microbiota driven by EEN in patients with ASUC receiving standard steroid therapy and examines correlations between EEN-associated bacteria and response to corticosteroid therapy. Methods: Stool samples were collected at baseline (Day0) and post-therapy (Day 7) from 44 patients with ASUC who received either SOC (n=24) or SOC supplemented with EEN (n=20) for a period of 7 days, at baseline (Day 0) and post-therapy (Day-7). Microbiome characterization was carried out using 16S rRNA gene sequencing followed by data processing using QIIME2 and R packages to analyze diversity and differentially abundant taxa. Results: Seven-day EEN supplementation of SOC in patients with ASUC resulted in enhanced proportions of Methylobacterium, Sphingomonas, Limosilactobacillus, Megamonas, Thermus, Viellonella, with a reduction in Ruminococcus gnavus, Gemmiger, Pseudomonas, and Enterococcus . EEN-mediated enhancement in specific taxa correlated positively with patients' day-7 serum albumin levels and negatively with day-3 faecal calprotectin levels (FCal) (Fig.1). Gut microbial composition of patients who responded to EEN-augmented SOC showed an enhanced abundance of Coprococcus, Megamonas, Oribacterium, Sediminibacterium, Acidibacter, and Thermus, and reduction in Sutterella, R. gnavus, Collinsella, Dorea, and Morganella, when compared to non-responders (Fig.2). Baseline gut microbiome signature in patients with ASUC predicts a potential response to both SOC and EEN-supplemented SOC in patients with ASUC (Fig.3). Conclusion: Augmentation of clinical response by EEN-conjugated corticosteroid therapy is accompanied by specific gut microbial changes in patients with ASUC.